2018
DOI: 10.1111/ppc.12261
|View full text |Cite
|
Sign up to set email alerts
|

Determination of physical health status and healthy lifestyle behaviors of individuals with mental illness

Abstract: Individuals with mental illness need to receive education and support, especially in terms of nutrition and exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…It was determined that there was no difference between spirituality and other descriptive variables except income level. The level of interpersonal relations sub-dimension was found to be higher than the other study in the literature (38). Interpersonal relations determine the communication of the individual with his or her immediate environment.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…It was determined that there was no difference between spirituality and other descriptive variables except income level. The level of interpersonal relations sub-dimension was found to be higher than the other study in the literature (38). Interpersonal relations determine the communication of the individual with his or her immediate environment.…”
Section: Discussioncontrasting
confidence: 63%
“…A literature review shows only one study using the same scale about the healthy lifestyle with persons with severe mental illness. In the study of Erginer and Günüşen (38), the highest scores in the healthy lifestyle scale were found in the spiritual development, interpersonal relationships and nutrition sub-dimensions, and the lowest scores were in the physical activity sub-dimension. The results of the two studies were parallel to each other.…”
Section: Discussionmentioning
confidence: 95%
“…In this sense, several studies have shown a direct relationship between physical activity and the components of healthy lifestyles, with one becoming the way to reach the other [28,29]. The lower the levels of physical activity, the poorer the healthy lifestyles [30] and the poorer the adherence to them [31].…”
Section: Introductionmentioning
confidence: 99%
“…This result supports H 3 . In a descriptive study conducted in XX using HLSBS II, it was found that individuals with SMI received the lowest HLSBS scores on the physical activity subscale 43 . In the literature, another study evaluating the results of interventions with a healthy lifestyle scale in mentally ill patients could not be encountered, and the changes in nutrition and physical activities of patients were evaluated with different measurement tools.…”
Section: Discussionmentioning
confidence: 99%